LATE LIFE DEPRESSION: A LITERATURE REVIEW OF LATE-LIFE DEPRESSION AND CONTRIBUTING FACTORS - Bulut, Sefa (Anales de Psicología / Annals of Psychology, 2009)
Literature provides a wide variety of information about food in-take, physical illness, and psychological disorders among the aging popula-tion. Late-onset of depression is one of the most common mental health problems in adults aged 60 or older. The primary purpose of this paper is to investigate the relationship between late-life depression and nutrition intake among older adults. Secondly, literature has indicated that late-life depression is influenced by genetic, situational, illness-related biological and psycho-social factors. However, late-life depression, relative to early-onset depression, appears to be less influenced by genetics and more in-fluenced by environmental factors. Psychological models postulate that late-life depression arises from the loss of self-esteem, loss of meaningful roles, loss of significant others, decline of social contacts, reduction of physical ability, financial difficulties and decline in coping skills. For these reasons, the contributing social, physical and psychological factors are briefly investigated in relation to nutritional aspects. Therefore, the scope of this paper will examine the social, physical, and psychological issues that directly or indirectly affect food intake and consequently depression in the elderly population.